Change the journal title to reflect evolving focus - Choi, Kyong; Lee, Yujin; Lee, Younhee; hwang, jihyun (Mathematics Education Research and Practice, 2025)
Research in Mathematics Education.This change reflects the journal's expanding scope, integrating both theoretical and practical aspects of mathematics education in alignment with growing interdisciplinary and applied academic trends.In this editorial, we discuss revised scope of MERP and invite contributions from a diverse range of researchers and practitioners
Keywords: Field (mathematics); Focus (optics); Range (aeronautics); Scope (computer science); dept.mat

Incorporating changeable attitudes toward vaccination into compartment models for infectious diseases - Jiang, Yi; Kurianski, Kristin; Lee, Jane; Ma, Yanping; Cicala, Daniel; Ledder, Glenn (Mathematical Biosciences & Engineering, 2025)
We develop a mechanistic model that classifies individuals both in terms of epidemiological status (SIR) and vaccination attitude (Willing or Unwilling/Unable), with the goal of discovering how disease spread is influenced by changing opinions about vaccination. Analysis of the model identifies the existence and stability criteria for both disease-free and endemic disease equilibria. The analytical results, supported by numerical simulations, show that attitude changes induced by disease prevalence can destabilize endemic disease equilibria, resulting in limit cycles.
Keywords: Computer science; Disease; Econometrics; Endemic disease; Environmental health; Epidemic model; Epidemiology; Immunology; Infectious disease (medical specialty); Limit (mathematics); Machine learning; Mathematics; Medicine; Pathology; Stability (learning theory); Vaccination; dept.mat

Rings with q-torsionfree canonical modules - Endo, Naoki; Ghezzi, Laura; Goto, Shiro; Hong, Jooyoun; Iai, Shin-Ichiro; Kobayashi, Toshinori; Matsuoka, Naoyuki; Takahashi, Ryo (Commutative Algebra, 2025)
Let A be a Noetherian local ring with canonical module KA. We characterize A when KA is a torsionless, reflexive, or q-torsionfree module for an integer q ≥ 3. If A is a Cohen–Macaulay ring, H.-B. Foxby proved in 1974 that the A-module KA is q-torsionfree if and only if the ring A is q-Gorenstein. With mild assumptions, we provide a generalization of Foxby’s result to arbitrary Noetherian local rings admitting the canonical module. In particular, since the reflexivity of the canonical module is closely related to the ring being Gorenstein in low codimension, we also explore quasinormal rings, introduced by W. V. Vasconcelos. We provide several examples as well. ©2025 Walter de Gruyter GmbH,Berlin/Boston.
Journal Abbreviation: De Gruyter Proc. Math.
Keywords: Algebra over a field; Canonical module; Class (philosophy); Cohen–Macaulay ring; Gorenstein ring; Representation (politics); Set (abstract data type); dept.mat; q-Gorenstein ring; q-torsionfree module; quasinormal ring

Hilbert coefficients and Sally modules: a survey of Vasconcelos’ contributions - Hong, Jooyoun; Morey, Susan (Commutative Algebra, 2025)
Keywords: Chern numbers; Data collection; Field (mathematics); Hilbert coefficients; Hilbert functions; Hilbert polynomials; Sally modules; Work (physics); dept.mat; multiplicity

Degrees: Vasconcelos contributions - Ghezzi, Laura; Hong, Jooyoun (De Gruyter Proc. Math., 2025)
A degree of a module M is a numerical measure of information carried by M. We highlight some of Vasconcelos’ outstanding contributions to the theory of degrees, bridging commutative algebra and computational algebra. We present several degrees he introduced and developed, including arithmetic degree, jdeg, homological degree, cohomological degrees, canonical degree, and bicanonical degree. For the canonical and bicanonical degrees, we discuss recent developments motivated by our joint works [25, 19, 9]. ©2025 Walter de Gruyter GmbH,Berlin/Boston.
Journal Abbreviation: De Gruyter Proc. Math.
Keywords: Multiplicity; arithmetic degree; bicanonical degree; canonical degree; canonical ideal; cohomological degree; dept.mat; homological degree; jdeg

Skolem Number of Kagome Lattice Graphs - Carrigan, Braxton; Martone, Max (Theory and Applications of Graphs, 2025)
A proper Skolem labelling of a graph G is a function assigning a positive integer to each vertex of G such that any two vertices assigned the same integer are that distance apart in the graph. The Skolem number of a graph is smallest number n such that there exists a proper Skolem labelling only using the positive integers less than or equal to n. In this paper, we will begin by proving the Skolem number for another family of subgraphs of the hexagonal lattice and then prove the Skolem number for two families of subgraphs of the Kagome Lattice. © 2025 Georgia Southern University. All rights reserved.
Keywords: dept.mat

On Tight 6-Cycle Decompositions of Complete 3-Uniform Multi-Hypergraphs - Bandell, Jessica A.; Bunge, Ryan C.; Darrow, Brian D.; El-Zanati, Saad I.; Mountain, Claire E.; Neiburger, Levi (Springer Proceedings in Mathematics and Statistics, 2025)
The λ-fold complete 3-uniform hypergraph on v vertices has the edge multiset consisting of λ copies of each 3-element subset of its vertex set. A tight 6-cycle, denoted TC6, is a hypergraph with vertex set {a,b,c,d,e,f} and edge set {{a,b,c},{b,c,d},{c,d,e},{d,e,f},{e,f,a},{f,a,b}}. We give necessary and sufficient conditions on v for the existence of a TC6-decomposition of the λ-fold complete 3-uniform hypergraph on v vertices for any positive integer λ. © The Author(s), under exclusive license to Springer Nature Switzerland AG 2025.
Journal Abbreviation: Springer Proc. Math. Stat.
Keywords: 3-uniform; Combinatorics; Computer science; Decomposition; Hypergraph; Mathematics; Multi-hypergraph; dept.mat